La posición de Tertuliano en el debate sobre las facultades del alma - Cresta, Norberto Gerald (Sapientia, 2023)
In his Treatise on the Soul (De anima), Tertullian addresses the question of the faculties of the soul, emphasizing the characterization of the rational soul. In contrast to the Platonic position, he adopts a philosophical-theological perspective that will be crucial in later developments of the subject and will become part of the doctrine regarding the soul in the authors of Latin scholasticism. Among his arguments, he introduces the fidelity of the senses, challenged by Plato and vindicated by the historical figure of Christ. This doctrinal position leads him to define the soul as produced from a source and of simple substance; thus, he criticizes, among other nuances, the dualism with its excessive valuation of the intellect over the senses, and the Platonic inconsistency that considered the soul as self-subsistent and at the same time capable of forgetting its previous state. The present work explores Tertullian's argumentative models against Greek philosophy and posits the hypothesis of an existential thought as a counterpart to philosophical formalism.